2010
DOI: 10.1007/s11154-010-9128-2
|View full text |Cite
|
Sign up to set email alerts
|

The economic consequences of diabetes and cardiovascular disease in the United States

Abstract: Diabetes-related care and complications constitute a significant proportion of the United States' (US) health care expenditure. Of these complications, cardiovascular disease (CVD) is a major component. Higher morbidity and mortality rates translate to higher costs of care in patients with diabetes compared to those who do not have the disease. Minorities bear a disproportionate burden of diabetes and CVD. We review this disparity and examine potential etiologies for it in Hispanics and African-Americans, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 119 publications
1
27
0
2
Order By: Relevance
“…5,6 The economic costs of diabetes to society are enormous, and the personal costs to affected patients in the form of long-term complications can be severe, especially among patients from socially disadvantaged backgrounds. 7 Treatment of diabetes involves adopting and maintaining complex treatment regimens encompassing pharmacotherapy, changes in diet, and physical activity. For patients to be able to implement these regimens, knowledge, motivation, training, and ongoing support are required as they attempt to change longentrenched behaviors.…”
Section: Elf-management Trainingmentioning
confidence: 99%
“…5,6 The economic costs of diabetes to society are enormous, and the personal costs to affected patients in the form of long-term complications can be severe, especially among patients from socially disadvantaged backgrounds. 7 Treatment of diabetes involves adopting and maintaining complex treatment regimens encompassing pharmacotherapy, changes in diet, and physical activity. For patients to be able to implement these regimens, knowledge, motivation, training, and ongoing support are required as they attempt to change longentrenched behaviors.…”
Section: Elf-management Trainingmentioning
confidence: 99%
“…It is estimated that nearly one-third of American adults are living with CMS (4), w10% of American adults have diabetes (5), and one-third of Americans adults have preexisting CVD (6). Type 2 diabetes and CVD in the United States account for over $600 billion annually in health care costs (7,8), which has been estimated to increase nearly 25% for each additional risk factor associated with CMS (9). Therefore, the management and prevention of CMS is of utmost public health and economic importance (10).…”
Section: Introductionmentioning
confidence: 99%
“…8,25 The top 5 diagnoses among patients with diabetes are congestive heart failure, coronary atherosclerosis, acute myocardial infarction, nonspecific chest pain, and cardiac dysrhythmia-all of which are costly diseases to treat. 8,[27][28][29] In this study, the control populations reported higher occurrences of several diseases associated with higher costs, including hypertension, osteoarthritis, osteoporosis, and rheumatoid arthritis, although the diabetes and control cohorts were matched on numerous characteristics. [30][31][32][33][34] However, patients with diabetes incurred higher costs overall.…”
Section: Discussionmentioning
confidence: 86%